Building Employee Performance and Retention Through Transformational Leadership Communication Behavior Via Trust and Motivation: An Analysis of Employees At PT Ace Hardware Indonesia Tbk - Dasep Suryanto; Niknik Ahmad Munawar; Crisdina Wempi; Mayang Lalita Ratri (Dinasti Publisher, 2023)
This study explores the impact of transformational leadership communication behavior at PT Ace Hardware Indonesia Tbk on employee trust, motivation, performance, and retention. A quantitative method was employed by distributing questionnaires to 300 company employees. Data collected from 300 employees at PT Ace Hardware Indonesia Tbk were analyzed using Smart PLS 3. The results indicate that transformational leadership communication behavior significantly influences employee trust, motivation, performance, and retention. Employee trust and motivation also play a significant role as mediators, mediating the influence of transformational leadership communication on employee performance and retention at PT Ace Hardware Indonesia Tbk. These findings depict a complex relationship among variables that mutually affect each other, providing profound insights into the crucial role of transformational leadership communication behavior in fostering positive relationships with employees. The outcomes of this research can serve as a foundation for companies to develop more effective strategies of transformational leadership, with a focus on enhancing employee trust and motivation. Practical implications include implementing leadership practices that strengthen positive relationships with employees. This study also contributes to the development of transformational leadership theory and provides directions for further research. Thus, the research not only benefits companies practically but also contributes to the academic knowledge development in the field of organizational leadership.